The silent crisis: Afghan women and the right to education - Shah, Sulman (Вестник Томского государственного университета)
This research investigates the challenges to Afghan women's education in Afghanistan under the rule of Taliban, focusing on cultural, socio-economic and political factors. Using a qualitative approach, it investigates secondary data from literature, policies and media to explore the historical evolution of the education of women and the effects of Taliban restrictions. The findings reveal that poverty, patriarchal norms and institutional discrimination strictly limit the access of education, in spite of Islamic teachings encouraging gender-equal education. The resilience of Afghan women is evident via online learning platforms and underground schools. The research underscores the Taliban's policies as opposing Islamic principles, which historically support women's educational and intellectual roles. It concludes with strategic recommendations, including international advocacy, community-led initiatives, and engagement with religious leaders, to restore educational rights. Wider implications emphasize education as fundamental human right and a source of socio-economic development. Future research should study effective application of these strategies and their continuing impact on gender equality.